2014
DOI: 10.1080/00206814.2014.941023
|View full text |Cite
|
Sign up to set email alerts
|

Consag Basin: northern Gulf of California, evidence of generation of new crust, based on seismic reflection data

Abstract: The Gulf of California is an excellent example of how new ocean basins form. Tectonically, the northern Gulf of California is an incipient ocean basin and studies on it have defined acoustic basement and reveal the presence of new oceanic crust and intrusive bodies. Some recent studies report fundamental differences between the basins of the northern and southern Gulf of California: that the latter have well-developed oceanic crust beneath a thin cover of sediments, whereas the northern basins show proto-ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…In the northern GoC, the nature and timing of continental rupture are still uncertain, with the presence of oceanic crust suggested in some basins (González‐Escobar et al, ; Martín‐Barajas et al, ) and delayed rupture suggested for others (Lizarralde et al, ; Martín‐Barajas et al, ). Deformation in the north is distributed across a pull‐apart structure between the Cerro Prieto Fault and the Ballenas Transfrom Fault Zone (Figure a; Persaud et al, ).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…In the northern GoC, the nature and timing of continental rupture are still uncertain, with the presence of oceanic crust suggested in some basins (González‐Escobar et al, ; Martín‐Barajas et al, ) and delayed rupture suggested for others (Lizarralde et al, ; Martín‐Barajas et al, ). Deformation in the north is distributed across a pull‐apart structure between the Cerro Prieto Fault and the Ballenas Transfrom Fault Zone (Figure a; Persaud et al, ).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…In the southernmost portion of the rift, the Alarcon basin has experienced seafloor spreading and the formation of oceanic crust with magnetic lineation since 3.5 Ma (Lonsdale, 1989). Further north, the Guaymas basin contains nearly 280 km of new oceanic crust under thick sedimentary deposits according to seismic refraction experiments, while the Delfín, Consag, and Wagner basins apparently have narrow troughs with oceanic crust under >6-km-thick sedimentary deposits from the Colorado River (González-Escobar et al, 2014;González-Fernández et al, 2005;Martín-Barajas et al, 2013;Persaud et al, 2003, Figure 1). These basins do not show obvious magnetic lineation (González-Fernández et al, 2005).…”
Section: Geodynamic and Volcano-tectonic Settingmentioning
confidence: 99%
“…As with the Salton Trough transects, adjustments are made to layer thicknesses in places that are not constrained by available data, or within uncertainties. Basement depths in the Wagner Basin transect are constrained using González-Escobar et al (2009) and González-Escobar et al (2014). Bathymetry is constrained by Bischoff and Niemitz (1980).…”
Section: Wagner Basinmentioning
confidence: 99%
“…Bathymetry is constrained by Bischoff and Niemitz (1980). The locations of the Wagner and Consag faults are obtained from González-Escobar et al (2009). Twoway travel times from seismic line 5023 from González-Escobar et al (2009) are used to estimate basement depth.…”
Section: Wagner Basinmentioning
confidence: 99%
See 1 more Smart Citation